ТРАНСПОРТНІ ХАБИ ЯК НОВІ ЦЕНТРИ ГЛОБАЛЬНОГО ВПЛИВУ - Ємчук, Тетяна Володимирівна; Цепенда, Микола Михайлович (ЕКОНОМІКА ТА СУСПІЛЬСТВО, 2025)
The purpose of this article is to examine the formation and functioning of transport hubs as emerging centers of global influence and to demonstrate their growing significance for the world economy and international relations. The relevance of the topic is explained by the fact that in the twenty-first century transport is no longer limited to technical operations of moving goods and passengers but has become a strategic instrument of economic development, political power, and integration into global trade networks. The study applies systemic, structural, and comparative methods which made it possible to analyze the features and dynamics of leading hubs, with Dubai, Singapore, and Rotterdam defined as the key objects of the research. The results show that Dubai has developed into a multifunctional aero-maritime cluster combining logistics, finance, and tourism, Singapore has consolidated its role as a global transshipment hub based on advanced automation and digitalization, while Rotterdam has become the gateway to Europe and an innovative energy-oriented hub. Despite their differences, all three cases demonstrate common characteristics such as advantageous geographical position, large-scale infrastructure investments, government support, and innovation-driven strategies. It is revealed that transport hubs are transforming from traditional nodes of transshipment into multifunctional clusters that influence supply chain resilience, shape the direction and stability of international trade flows, and generate new poles of economic growth. In addition, the analysis emphasizes that these hubs create powerful clustering effects, stimulate regional innovation, and attract global capital by concentrating trade, finance, and high technologies in one integrated spatial system. Practical value lies in the possibility of applying the conclusions of the study to the development of national strategies for transport infrastructure modernization, the improvement of logistics systems, and the strengthening of global competitiveness by transforming transport hubs into integrated centers of logistics, finance, innovation, and energy that act as decisive drivers of economic and geopolitical development; the recommendations outlined also provide guidance for policymakers, port authorities, and logistics operators in adapting to global megatrends and ensuring long-term resilience.
Keywords: транспортні хаби; глобальний вплив; логістика; геополітика; інновації; енергетичний перехід